2017
DOI: 10.25115/ejrep.v9i23.1431
|View full text |Cite
|
Sign up to set email alerts
|

Are fourth and fifth grade children better scientists through metacognitive learning?

Abstract: Introduction. A way to find out how scientific thinking in children develops is to focus on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Araştırma sorgulamaya dayalı öğrenmede öğrencilerin problem çözme stratejileri, bilişsel ve üst bilişsel stratejileri kullanma yoluyla aktif rol almaları öz-düzenlemeyi sağlar (Dejonckheere, Van de Keere & Tallir, 2011). Öz-düzenleme, bireyin düşünme, problem çözme ve davranışta bulunma için gerekli olanları içselleştirmesidir.…”
Section: Introductionunclassified
“…Araştırma sorgulamaya dayalı öğrenmede öğrencilerin problem çözme stratejileri, bilişsel ve üst bilişsel stratejileri kullanma yoluyla aktif rol almaları öz-düzenlemeyi sağlar (Dejonckheere, Van de Keere & Tallir, 2011). Öz-düzenleme, bireyin düşünme, problem çözme ve davranışta bulunma için gerekli olanları içselleştirmesidir.…”
Section: Introductionunclassified
“…At the end, we added a reflecting step, which was used as a metacognitive tool. This latter step was added because Dejonckheere, Van de Keere, and Tallir (2011) have shown that 11-year-old children who were taught to design a scientific experiment together with metacognitive support outperformed those who did not receive such support.…”
Section: The Inclu-s-ed Studymentioning
confidence: 99%
“…Students are able to engage in this process as conscious learners who can regulate their acquisition of information and motivate themselves to overcome failures in their learning processes (Dejonckheere, Van De Keere, & Tallir, 2011). Students may hereby enhance their understanding of how successful learning occurs (Balcikanli, 2011;Forlin, 2010;Gaeta, Teruel, & Orejudo, 2012).…”
Section: Introductionmentioning
confidence: 99%